Aerobic Gymnastics Intervention on BMI, Abdominal Circumference and Lipid Profile in DMPA Acceptance - Khobibah Khobibah; Budi Astyandini; Mimi Ruspita (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
The risk of obesity and hypertension is associated with the influence of the hormone estrogen and the impact of the use of contraceptives. Use over one year is at risk of 1.36 times overweight, and will continue to increase in use over seven years (8.3 times). An important component for weight loss is aerobic exercise, so expected BMI, triglycerides, total cholesterol. LDL and HDL under normal conditions. Interventions in the form of treadmills, aerobic gymnastics or ergocycle. The purpose of this study is to determine the influence of aerobic gymnastics BMI, abdominal circumference and lipid profile of KB DMPA acceptors. The design was the quasi-experimental research (one group pretest posttest design). Pretest BMI, abdominal circumference, cholesterol, HDL and LDL were performed before and after the acceptor performed aerobic gymnastics a total of 16 meetings with a frequency of 3 times per week. The sample numbered 31 people. Data analysis using t-test and Wilcoxon. The results showed that aerobic gymnastics had no significant effect on BMI (p=0.818) and HDL (p=0.416) but had no significant effect on decreased abdominal fat (p=0.002), cholesterol (p = 0.044) and LDL (p=0.030). This recommendation of research is the need for routine physical activity such as aerobic gymnastics for DMPA KB acceptors so as to reduce complaints due to the side effects of DMPA contraceptives.